Изменения цитокинового профиля крови при экспериментальном диффузном кардиосклерозе у крыс с различной устойчивостью к гипоксии = Changes of cytokine blood profile in experimental diffuse cardiosclerosis in rats with different resistance to hypoxia - H. S. Saturska; Yu. I. Bondarenko; V. E. Pelykh (Kazimierz Wielki University, 2015)
Saturska H. S., Bondarenko Yu. I., Pelykh V. E. Изменения цитокинового профиля крови при экспериментальном диффузном кардиосклерозе у крыс с различной устойчивостью к гипоксии = Changes of cytokine blood profile in experimental diffuse cardiosclerosis in rats with different resistance to hypoxia. Journal of Education, Health and Sport. 2015;5(2):66-78. ISSN 2391-8306. DOI: 10.5281/zenodo.15412 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A66-78 https://pbn.nauka.gov.pl/works/536525 http://dx.doi.org/10.5281/zenodo.15412 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.   УДК 616.12-004-097-02:616.152.21]-092.9 UDC 616.12-004-097-02:616.152.21]-092.9 ИЗМЕНЕНИЯ ЦИТОКИНОВОГО ПРОФИЛЯ КРОВИ ПРИ ЭКСПЕРИМЕНТАЛЬНОМ ДИФФУЗНОМ КАРДИОСКЛЕРОЗЕ У КРЫС С РАЗЛИЧНОЙ УСТОЙЧИВОСТЬЮ К ГИПОКСИИ Changes of cytokine blood profile in experimental diffuse cardiosclerosis in rats with different resistance to hypoxia Сатурская А. С., Бондаренко Ю. И., Пелых В. Е. Saturska H. S., Bondarenko Yu. I., Pelykh V. E. ГВУЗ «Тернопольский государственный медицинский университет имени И.Я. Горбачевского МЗ Украины», г. Тернополь SHEI "I. Horbachevsky Ternopil State Medical University of the Ministry of Public Health of Ukraine", Ternopil, Ukraine saturska.gs@gmail.com   Ключевые слова: гипоксия, диффузный кардиосклероз, цитокины. Key words: hypoxia, diffuse myocardial fibrosis, cytokines.   Резюме   В работе изложены особенности изменений цитокинового статуса в динамике развития экспериментального кардиосклероза у лабораторных животных (белых крыс) с различной устойчивостью к гипоксии на этапах моделирования данной патологии (7, 14, 30 суток наблюдения). Выявлено, что развитие кардиосклеротического процесса сопровождается различным по степени повышением синтеза цитокинов - ИЛ-1β, ИЛ-6 в зависимости от чувствительности животных к гипоксии, а также от периода наблюдения. Особенностями реакции противовоспалительного звена на моделирование диффузного кардиосклероза является повышение содержания ИЛ-10 на всех этапах развития патологии, за исключением низкоустойчивых к гипоксии животных, у которых содержание ИЛ-10 немного снижено.   Abstract   The article presents peculiarities of changes of cytokine status in the dynamics of experimental cardiosclerosis in laboratory animals (white rats) with different resistance to hypoxia at stages of modeling of the disease (7, 14, 30 days of observation). It has been discovered that the development of experimental diffuse ischemic necrotic cardiosclerosis is accompanied by different degrees of increase of synthesis of IL-1β and IL-6 cytokines in blood serum depending on the sensitivity of animals to hypoxia and on the observation period. Increased level of IL-10 inblood serum in animals with high and medium resistance to hypoxia at all stages of the disease, and decreased level of IL-10 inblood serum in animals with low resistance to hypoxia are the main peculiarities of an anti-inflammatory response due to diffuse cardiosclerosis modeling.